THE FOUCAULT-PENDULUM - Szaladnya, Sándor (Advanced Logistic Systems - Theory and Practice, 2018)
In the material handling, there are many machines in which the goods can swing during transport or loading. The greatest impact of this phenomenon is appearing during the operation of different cranes, where the goods are moving as a pendulum. In 1851, Jean Foucault presented a strand-pendulum, which was used to demonstrate the rotation of the Earth. This Foucault-pendulum and its describing equations can help to understand the behaviour of the swinging bodies and the rules which influence their movement. In this paper, the author presents the importance and the essential formulas to describe the behaviour of a pendulum, using the data of the Foucault-pendulum built at the main entrance of the University of Miskolc as a reference object.